2004
DOI: 10.14412/1995-4484-2004-1469
|View full text |Cite
|
Sign up to set email alerts
|

Ovarial function in pts with systemic lupus erythematosus

Abstract: ГУ Институт ревматологии РАМН, Москва Резюме Цель. Оценить овариальную функцию больных системной красной волчанкой (СКВ) и влияние на нее терапии циклофосфаном (ЦФ). Материал и методы. Обследовано 44 пациентки с СКВ в возрасте от 16 до 45 лет с сохранным менструальным циклом. Из них 18 ранее получали терапию ЦФ в средней кумулятивной дозе 5,7 г, 26-никогда не принимали ЦФ. Средние значения возраста, длительности, активности за болевания (по шкале SLEDAI) и доз глюкокортикоидов (ГК) были сходными в обеих группа… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
4
35
1
4
Order By: Relevance
“…It predominantly affects young adults (median age at diagnosis < 40 years), and women with SLE have a higher risk of developing menstrual irregularities compared with a healthy population. [1][2][3] In patients with irregular cycles, the mean SLE disease activity index (SLEDAI) levels and the frequency of patients with SLEDAI ‡ 8 were found to be significantly higher 2 than in patients with regular cycles, and the disease activity was shown to be a major factor associated with menstrual cycle disorders in SLE patients before treatment with alkylating agents, 3 so the high SLEDAI levels were associated with impaired ovarian function. There was also a higher risk of patients having an irregular cycle after cyclophosphamide (CTX) therapy, as this therapy is known to damage ovarian follicles.…”
mentioning
confidence: 99%
“…It predominantly affects young adults (median age at diagnosis < 40 years), and women with SLE have a higher risk of developing menstrual irregularities compared with a healthy population. [1][2][3] In patients with irregular cycles, the mean SLE disease activity index (SLEDAI) levels and the frequency of patients with SLEDAI ‡ 8 were found to be significantly higher 2 than in patients with regular cycles, and the disease activity was shown to be a major factor associated with menstrual cycle disorders in SLE patients before treatment with alkylating agents, 3 so the high SLEDAI levels were associated with impaired ovarian function. There was also a higher risk of patients having an irregular cycle after cyclophosphamide (CTX) therapy, as this therapy is known to damage ovarian follicles.…”
mentioning
confidence: 99%
“…Several studies including a nurse health study for oral contraceptive use have shown an increase of 1.9 time SLE manifestations compared to non users (Sanchez-Guerrero et al, 1995) and similar effect have been demonstrated with HRT (Cooper et al, 2002). In addition a lot of evidence is showing that the SLE manifestations are correlated with ovarian cycle alterations (Shabanova et al, 2008). A clear link is seen between hormonal changes and SLE therefore higher vigilance is sought for SLE women willing to become pregnant.…”
Section: Systemic Lupus Erythematosus 211 Pathophysiology Of Slementioning
confidence: 90%
“…выявили повышение содер-жания активного метаболита эстрогенов -16α-гидрокси-эстрона, тогда как только женщины с СКВ и мужчины с синдромом Клайнфельтера (дополнительная X-хромосо-ма) имели повышенные уровни как 16α-гидроксиэстрона, так и эстриола [50]. Доказано, что эти метаболиты эстради-ола (16α-гидроксиэстрон и эстриол) оказывают стимули-рующее влияние на течение СКВ за счет высокой эстро-генной активности [51], а содержание эстрадиола при СКВ может быть как повышенным, так и пониженным [52,53]. Эти данные подтверждают гипотезу о нарушении проме-жуточных звеньев метаболизма эстрогенов и тестостерона при СКВ [53].…”
unclassified
“…Для женщин с СКВ характерно снижение концентрации в кро-ви прогестерона и его метаболита -17-гидроксипрогесте-рона [52,84]. По нашим данным, у половины обследован-ных женщин с СКВ тоже определялось снижение уровня прогестерона в крови, ассоциируемое с высокой активно-стью заболевания [52]. Следовательно, можно рассматри-вать возможность применения прогестерона в терапии ау-тоиммунных заболеваний, включая СКВ [83], но данный вопрос остается пока малоизученным.…”
unclassified